Language Development Profile in Children Under Five Years Old: A Literature Review - Agung S, M Panji (International Journal of Linguistics, Communication, and Broadcasting, 2024)
Language development in humans is part of cognitive development. Children's language development is a process in which they acquire the ability to understand and communicate through speech. Before achieving fluency, a child may gradually comprehend basic verbal patterns and enhance their vocabulary during this stage. Children's grammar development progresses from one word or sentence, but some sentences, especially those with prepositional phrases, rules, and plurals, need correction. Early language development involves many errors, so parents must patiently correct mistakes. Language development in early childhood is fundamental. This paper aims to review the language development profile in children under the age of five. The research method used is literature review and library research. The results show that the language development profile in children under five follows stages that include word usage in sentences and comprehension building.